Modulation of growth characteristics and endogenous hormone by cutting intensity in Eleutherococcus giraldii - Xufeng Huang; Rui Gu; Guopeng Chen; Chenhui Wang; Yuan Li; Xiaofeng Liang; Rong Dimg; Shihong Zhong (PLoS ONE, 2025)
Eleutherococcus giraldii (E. giraldii) is a quintessential medicinal plant in traditional Chinese medicine. This study established control, heavy pruning, and light pruning groups to reveal growth indexes and endogenous phytohormones in cultivated E. giraldii using enzyme-linked immunosorbent assay (ELISA). Results indicated that light pruning significantly promoted length of new branch elongation, thereby increasing E. giraldii branch bark yield. In contrast, heavy pruning inhibited length of new branch elongation and reduced branch bark production. Both pruning intensities enhanced the number and length of newly sprouted clonal plants, facilitating population expansion of E. giraldii. The heavy pruning altered the trends of indoleacetic acid (IAA) and abscisic acid (ABA) in apical leaves, as well as IAA and gibberellic acid 3 (GA3) in lateral leaves. The light pruning modified the trends of IAA, ABA, and isopentenyl adenine nucleoside (iPA) in apical leaves, as well as IAA and GA3 in lateral leaves. Apical leaf IAA promoted new branch growth in E. giraldii, while lateral leaf IAA exhibited the opposite effect. iPA played a significant role in eliminating apical dominance and enhancing stress resistance in E. giraldii. GA3 inhibited new branch growth while delaying leaf senescence. Apical leaf ABA was closely associated with improved stress resistance, whereas lateral leaf ABA primarily inhibited new branch growth. This study provides valuable insights for establishing sustainable logging strategies for E. giraldii, protecting wild resources, and offers reference for research on endogenous hormone responses in shrubs under logging interventions.